Assessment of short-term intraocular pressure parameters in phakic and pseudophakic patients with primary open-angle glaucoma - Lourenço,Adriana Sobral (2021)
ABSTRACT Purpose: To investigate intraocular pressure peaks in phakic and pseudophakic patients with primary open-angle glaucoma. Method: Overall, 40 patients with primary open-angle glaucoma were assessed. Of these, 20 patients were phakic and 20 pseudophakic. One eye (randomly selected) was included in the study. All patients underwent the intraocular pressure curves test, followed by the water-drinking test. Results: A statistically significant difference was observed between the phakic and pseudophakic patients regarding the mean of the peaks in the intraocular pressure curves (p=0.045). A statistically significant intergroup difference was noted regarding the intraocular pressure peaks in the water-drinking test, with higher values observed in the phakic patients (p 0.004). Conclusion: The intraocular pressure peaks in the water-drinking test and intraocular pressure curves were higher in the phakic group than in the pseudophakic group.